Enhanced large-scale production of recombinant phytase in E. coli DH5 α: medium components optimization and thermodynamic studies - Nuge, Tamrin; Hayyan, Adeeb; Elgharbawy, Amal A.M.; Mohd. Salleh, Hamzah; Yap, Jun Yong; Kamarudin, Ainul Fitree; Hizaddin, Hanee Farzana; Hashim, Yumi Zuhanis Has-Yun; Liu, Xiaoling; Saleh, Jehad; Daoud, Jamal Ibrahim; Aljohani, Abdullah S. M.; et al. (Elsevier, 2023)
Medium components and their solubility for improvement of recombinant phytase production in Escherichia coli DH5α. was optimized and reported in this study. Solubility study was supported by the computational works conducted using COSMO-RS, a quick tool to predict the thermophysical and chemical properties of fluid mixture. Solubility concept through thermodynamic calculation was introduced to study the interaction between medium components with water and selected medium components with each other. Based on the σ-profile and σ-potential, together with Gibbs free energy, a less soluble medium component showed a negative effect on phytase production due to the formation of insoluble metal-ion phytate complexes. Highest phytase production was obtained under optimum conditions of as 30 g/L yeast extracts, 1 g/L (NH4)2HPO4, 3 g/L MgSO4·7H2O, 0.3 g/L FeSO4·7H2O and 0.1 % (v/v) glycerol. Both experimental and computational works were conducted to investigate the interaction between medium components. The melting point and phase appearance of the mixture were studied. From experimental results, the mixtures were seemed to be unstable due to its higher melting point compared to individual medium components. The analysis from Gibbs free energy reflected the total immiscibility between medium components. It was concluded that medium components worked individually to promote the phytase production. Yeast extract, MgSO4·7H2O and FeSO4·7H2O were selected for optimization by central composite design, whereas other factors were maintained at their optimal level. Statistical analysis showed that the optimum media containing 34.06 g/L yeast extract, 3.6 g/L MgSO4·7H2O and 0.32 g/L FeSO4·7H2O gave the maximum phytase production of 118.91 U/mL. The optimization of process condition such as temperature, agitation speed and seed age were further investigated by employing Full Factorial Experimental (FUFE) Design after fixing the media composition. The maximum phytase production of 200 U/mL was obtained at optimum condition (temperature 37 °C, agitation speed 500 rpm and seed age 1.55 at OD600nm). The phytase production in a larger scale was conducted by submerged fermentation in 2 L and 30 L bioreactor. In large scale production, constant tip speed suited the best for scale-up strategy comparing to the constant power number. The optimum process condition improved the phytase production and plasmid stability.